Innovative Activity as the Main Factor of Educational Efficiency - Shamatov Bakhriddin Valiyevich (Periodica Journal, 2023)
One of the main tasks of the education system is to train and educate free-thinking, creative, active and all-round highly qualified personnel based on modern educational programs. Only a creative, professional teacher with high pedagogical skills, armed with modern innovative technologies can train such a pupil or student. In this sense, this article is also directly devoted to the issues of directing teachers to innovative activities.
Keywords: innovation; educational system; continuous education